Step
*
1
1
of Lemma
fdl-is-1_wf
1. X : Type
2. X List List ∈ Type
3. ∀as,bs:X List List.  (dlattice-eq(X;as;bs) ∈ Type)
4. ∀as:X List List. dlattice-eq(X;as;as)
5. EquivRel(X List List;as,bs.dlattice-eq(X;as;bs))
6. as : X List List@i
7. bs : X List List@i
8. as 
⇒ bs
9. bs 
⇒ as
⊢ fdl-is-1(as) = fdl-is-1(bs)
BY
{ Assert ⌜∀as,bs:X List List.  (bs 
⇒ as 
⇒ (↑(∃a∈as.isaxiom(a))_b) 
⇒ (↑(∃a∈bs.isaxiom(a))_b))⌝⋅ }
1
.....assertion..... 
1. X : Type
2. X List List ∈ Type
3. ∀as,bs:X List List.  (dlattice-eq(X;as;bs) ∈ Type)
4. ∀as:X List List. dlattice-eq(X;as;as)
5. EquivRel(X List List;as,bs.dlattice-eq(X;as;bs))
6. as : X List List@i
7. bs : X List List@i
8. as 
⇒ bs
9. bs 
⇒ as
⊢ ∀as,bs:X List List.  (bs 
⇒ as 
⇒ (↑(∃a∈as.isaxiom(a))_b) 
⇒ (↑(∃a∈bs.isaxiom(a))_b))
2
1. X : Type
2. X List List ∈ Type
3. ∀as,bs:X List List.  (dlattice-eq(X;as;bs) ∈ Type)
4. ∀as:X List List. dlattice-eq(X;as;as)
5. EquivRel(X List List;as,bs.dlattice-eq(X;as;bs))
6. as : X List List@i
7. bs : X List List@i
8. as 
⇒ bs
9. bs 
⇒ as
10. ∀as,bs:X List List.  (bs 
⇒ as 
⇒ (↑(∃a∈as.isaxiom(a))_b) 
⇒ (↑(∃a∈bs.isaxiom(a))_b))
⊢ fdl-is-1(as) = fdl-is-1(bs)
Latex:
Latex:
1.  X  :  Type
2.  X  List  List  \mmember{}  Type
3.  \mforall{}as,bs:X  List  List.    (dlattice-eq(X;as;bs)  \mmember{}  Type)
4.  \mforall{}as:X  List  List.  dlattice-eq(X;as;as)
5.  EquivRel(X  List  List;as,bs.dlattice-eq(X;as;bs))
6.  as  :  X  List  List@i
7.  bs  :  X  List  List@i
8.  as  {}\mRightarrow{}  bs
9.  bs  {}\mRightarrow{}  as
\mvdash{}  fdl-is-1(as)  =  fdl-is-1(bs)
By
Latex:
Assert  \mkleeneopen{}\mforall{}as,bs:X  List  List.    (bs  {}\mRightarrow{}  as  {}\mRightarrow{}  (\muparrow{}(\mexists{}a\mmember{}as.isaxiom(a))\_b)  {}\mRightarrow{}  (\muparrow{}(\mexists{}a\mmember{}bs.isaxiom(a))\_b))\mkleeneclose{}\mcdot{}
Home
Index